Library users' practices and engagement in digital library resources (DLRs) in selected universities in Morogoro, Tanzania - Mbugunde, Neila; M’Kulama, Abel (Tanzania Journal of Community Development, 2026)
In higher education, digital library resources (DLRs) are increasingly recognized as vital tools for academic success. Their effective utilization, however, depends not only on availability but also on how users practice and engage with these resources. This study examined library users’ practices and engagement with DLRs in selected universities in Morogoro, Tanzania. A cross sectional survey design was employed, involving 150 respondents through questionnaires, 89 participants in 10 Focus Group Discussions (FGDs), and 16 key informants through interviews. Quantitative data were analyzed using IBM SPSS version 20, while qualitative data were thematically organized in line with the study objectives. Findings reveal that the majority of users (68%) reported moderate engagement with DLRs, while 18% reported high engagement and 14% reported low engagement. In terms of device ownership, most respondents owned between one and three devices, with 62% classified under moderate ownership, 24% under low ownership, and 14% under high ownership. However, chi square tests showed no significant association between device ownership and either self-rated digital literacy or knowledge of DLRs, indicating that ownership alone does not determine competence. Knowledge levels of DLRs were generally limited: 40% reported inadequate knowledge, 26% moderate knowledge, and only 34% adequate knowledge. Similarly, engagement practices did not significantly correspond to higher knowledge levels, suggesting that usage patterns alone do not guarantee deeper understanding. Employment status, however, was significantly associated with engagement, with faculty members more likely to report high practices compared to students and administrative staff. The study concludes that while moderate engagement and ownership are dominant trends, insufficient knowledge and awareness constrain effective adoption of DLRs. It recommends intensified information dissemination, sensitization programs, and targeted training initiatives to enhance users’ understanding and awareness, thereby fostering greater utilization of DLRs and improving academic outcomes